Environmental Governance of the Baltic Sea - Gilek, Michael; Karlsson, Mikael; Linke, Sebastian; Smolarz, Katarzyna; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This edited volume presents a comprehensive and coherent interdisciplinary analysis of challenges and possibilities for sustainable governance of the Baltic Sea ecosystem by combining knowledge and approaches from natural and social sciences. Focusing on the Ecosystem Approach to Management (EAM) and associated multi-level, multi-sector and multi-actor challenges, the book provides up-to-date descriptions and analyses of environmental governance structures and processes at the macro-regional Baltic Sea level. Organised in two parts, Part 1 presents in-depth case studies of environmental governance practices and challenges linked to five key environmental problems - eutrophication, chemical pollution, overfishing, oil discharges and invasive species. Part 2 analyses and compares governance challenges and opportunities across the five case studies, focusing on governance structures and EAM implementation, knowledge integration and science support, as well as stakeholder communication andparticipation. Based on these cross-case comparisons, this book also draws a set of general conclusions on possible ways of improving the governance of the Baltic Sea by promoting what are identified as vital functions of environmental governance: coordination, integration, interdisciplinarity, precaution, deliberation, communication and adaptability. .
Chapter 1. Environmental Governance of the Baltic Sea: Identifying Key Challenges Research Topics and Analytical Approaches. Part 1: Interdisciplinary Case Studies of Environmental Governance -- Chapter 2. Eutrophication and the Ecosystem Approach to Management: A Case Study of Baltic Sea Environmental Governance -- Chapter 3. Fisheries: A Case Study of Baltic Sea Environmental Governance -- Chapter 4. Biological Invasions: a Case Study of Baltic Sea Environmental Governance -- Chapter 5. Governance of Chemicals in the Baltic Sea Region: A Study of Three Generations of Hazardous Substances -- Chapter 6. Oil Spills from Shipping: A Case Study of the Governance of Accidental Hazards and Intentional Pollution in the Baltic Sea -- Part 2: Cross-Case Analysis of Key Environmental Governance Challenges -- Chapter 7. The Ecosystem Approach to Management in Baltic Sea Governance: Towards Increased Reflexivity? -- Chapter 8. Science-Policy Interfaces in Baltic Sea Environmental Governance: Towards Regional Cooperation and Management of Uncertainty? -- Chapter 9. Risk Communication and the Role of the Public: Towards Inclusive Environmental Governance of the Baltic Sea? -- Chapter 10. Seeking Pathways Towards Improved Environmental Governance of the Baltic Sea.
Keywords: Environmental management; Political science; Water; Hydrology; Animal culture; Environmental Management; Political Science; Water; Animal Science